Meat and haem iron intake in relation to glioma in the European Prospective Investigation into Cancer and Nutrition study. Issue 4 (July 2018) - Ward, Heather A.; Gayle, Alicia; Jakszyn, Paula; Merritt, Melissa; Melin, Beatrice; Freisling, Heinz; Weiderpass, Elisabete; Tjonneland, Anne; Olsen, Anja; Dahm, Christina C.; Overvad, Kim; Katzke, Verena; et al.
Abstract : Diets high in red or processed meat have been associated positively with some cancers, and several possible underlying mechanisms have been proposed, including iron-related pathways. However, the role of meat intake in adult glioma risk has yielded conflicting findings because of small sample sizes and heterogeneous tumour classifications. The aim of this study was to examine red meat, processed meat and iron intake in relation to glioma risk in the European Prospective Investigation into Cancer and Nutrition study. In this prospective cohort study, 408 751 individuals from nine European countries completed demographic and dietary questionnaires at recruitment. Multivariable Cox proportional hazards models were used to examine intake of red meat, processed meat, total dietary iron and haem iron in relation to incident glioma. During an average follow-up of 14.1 years, 688 incident glioma cases were diagnosed. There was no evidence that any of the meat variables (red, processed meat or subtypes of meat) or iron (total or haem) were associated with glioma; results were unchanged when the first 2 years of follow-up were excluded. This study suggests that there is no association between meat or iron intake and adult glioma. This is the largest prospective analysis of meat and iron in relation to glioma and as such provides a substantial contribution to a limited and inconsistent literature.